Bullying in an islamic perspective: integration of islamic values in the midst of a national bullying crisis - Sindi Ayudia Pama; Anisa Siti Nurjanah; Boy Haryono (RedWhite Press, 2025)
Bullying in educational settings constitutes a serious psychosocial risk, with Indonesia reporting a rapid escalation in documented cases. Despite the availability of psychological intervention frameworks, secular counseling approaches have demonstrated limited cultural resonance in majority-Muslim contexts. This study systematically reviews the literature on bullying from an Islamic perspective, with the aim of synthesizing scholarly evidence on how Islamic values can be integrated into guidance and counseling services as a framework for bullying prevention. A thematic literature review was conducted using Google Scholar, DOAJ, Dimensions, and Crossref, with search strings combining ('bullying' OR 'school bullying' OR 'cyberbullying') AND ('Islam' OR 'Islamic values' OR 'Islamic counseling' OR 'maqasid sharia'). Seventy-one sources published between 2017 and 2024 were screened; 22 met the inclusion criteria. Thematic analysis following Braun and Clarke's (2006) six-phase framework yielded five major themes. Findings indicate that Islamic jurisprudence provides a comprehensive normative prohibition against bullying through Qur'anic injunctions (QS Al-Hujurat 49:11; QS Al-Humazah 104:1; QS Al-Ahzab 33:58) and prophetic traditions. The maqasid al-shari'ah framework identifies bullying as a direct threat to five protected interests: religion, life, intellect, lineage, and property. The values of rahmah (compassion), 'adl (justice), ukhuwah (brotherhood), tazkiyah (purification), and karamah (human dignity) map coherently onto established psychological constructs of empathy, fair treatment, social connectedness, self-regulation, and respect all demonstrated to reduce bullying propensity. The integration of Islamic values in school counseling is not merely a normative proposition; it offers a culturally grounded and empirically plausible framework that complements social-psychological theories. Schools in Muslim-majority contexts are encouraged to adopt integrative counseling models that embed these values into preventive and restorative interventions.